Solvothermal Synthesis of Flower-Flakes Like Nano Composites of Ni-Co Metal Organic Frameworks and Graphene Nanoplatelets for Energy Storage Applications. (5th January 2022) - Abdul Karim, Muhammad Ramzan; Noman, Muhammad; Khan, Khurram Imran; Shehzad, Waseem; Haq, Ehsan Ul; Shahzad, Nadia; Yaqoob, Khurram
Abstract : Solvothermal synthesis of Ni-Co-metal organic framework (MOF)/graphene nanoplatelets (GNPs) nanocomposites was done for their potential application as electrode material in energy storage devices. Addition of GNPs and metallic precursors together with 2-methylimedazole in the same autoclave reactor produced smooth-nanoflakes like Ni-Co-MOF/GNPs nanocomposites as evaluated by scanning electron microscopy (SEM). X-ray diffraction (XRD) analysis showed the presence of GNPs where GNPs do not affect the growth of MOF crystals and Ni-Co-MOF crystalline phases remain unaffected in the composite structure. Fourier transform infrared (FTIR) spectroscopy analysis confirmed the presence of organic links forming nickel-cobalt metal cations framework. Electrochemical testing (CV, EIS and GCD) of the produced composites demonstrated that GNPs addition can enhance the charge storage performance of MOF nanocomposites. The largest cycle area and most discharge time have been shown by Ni-Co-MOF/GNP-50 composite electrode that delivered the highest specific capacity values (313Cg −1 @1Ag −1 ), good reversibility and low internal resistance and charge transfer resistance, owing to efficient dispersion of flower-like flaky particles and efficient interconnected paths for ion and electron transportation. Moreover, Ni-Co-MOF/GNP-50 composite exhibited good thermal stability with 28% weight loss during thermogravimetric analysis. The electrochemical evaluations performed on asymmetric supercapacitor (ASC) real device expressed a specific capacity of 136.5 Cg −1 @0.5Ag −1, maximum energy density of 32.2 Whkg −1 @425 Wkg −1 and maximum power density of 17000 Wkg −1 @12.8 Whkg −1 . Moreover, the device showed a stability performance of 92.5%@10 Ag −1 after 5000 CD cycles.